The Vermeer exhibition of 1935 a major debut in historical perspective - Rinnooy Kan, Justine (2021)
In 1935, Museum Boymans (now Museum Boijmans Van Beuningen) in Rotterdam held the first major loan exhibition devoted to Johannes Vermeer (1632-1675) and the Delft school. It was curated by director Dirk Hannema (1895-1984), on the occasion of the opening of the new museum building. Through the research of archival material, this article explores the origin, concept, execution and reception of the exhibition, with a focus on Hannema as the driving force behind it. The exhibition was a great success. It was critically acclaimed, and together with the new building it strengthened the reputation of Museum Boymans and Dirk Hannema. The exhibition concept addressed the pressing academic issue of Vermeer’s early artistic development, and offered scholars a chance to visually study this topic. Thanks to the rich selection of 142 paintings by over 35 painters, coming from over seventy collections, the event was also a fruitful opportunity to study seventeenth-century Delft painting and to clarify problems of attribution. The high quality of the illustrated catalogue further facilitated the advancement of knowledge about the exhibited works and artists. In monographic literature about Vermeer, this historic exhibition is overshadowed by the Van Meegeren scandal of Vermeer forgeries, despite the fact that it took place in the years following the exhibition, from 1937 onwards. The well-documented affair shaped the way people now think about both Vermeer connoisseurship in the 1930s and 1940s, as well as the legacy of Dirk Hannema. In addition to offering readers a comprehensive understanding of the exhibition, this article aims to demonstrate that the silence surrounding the exhibition in monographic literature about Vermeer does not reflect its contribution to knowledge about the artist.
Keywords: Vermeer van Delft, Jan -- 1632-1675; Hannema, Dirk -- 1895-1984; Museum Boijmans van Beuningen; Geschichte 1935-1950; Geschichte 1935; Malerei; Kunstfälschung; Ausstellung; Delft